2023
DOI: 10.3389/fsurg.2022.927491
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of postoperative neutrophil-to-lymphocyte ratio, D-dimer, and CA153 in: Diagnostic value for recurrent and metastatic breast cancer

Abstract: ObjectiveThis stydy aims to assess the value of monitoring of postoperative neutrophil-to-lymphocyte ratio (NLR), D-dimer, and carbohydrate antigen 153 (CA153) for diagnosis of breast cancer (BC) recurrence and metastasis.Materials/MethodsA cohort of 252 BC patients who underwent surgery at the First Affiliated Hospital of Anhui Medical University between August 2008 and August 2018 were enrolled in this retrospective study. All patients were examined during outpatient follow-ups every 3 months for 5 years pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…The postoperative NLR holds notable prognostic significance and merits attention in oncological investigations; it can reflect the systemic inflammatory response following tumor removal, providing insights into the host immune response, modulation of the tumor microenvironment and residual disease burden. Previous studies reported that elevated NLR levels, both immediately within 1 week postoperatively and later, 5 years after diagnosis, were associated with poorer survival outcomes in BC ( 51 53 ).…”
Section: Discussionmentioning
confidence: 92%
“…The postoperative NLR holds notable prognostic significance and merits attention in oncological investigations; it can reflect the systemic inflammatory response following tumor removal, providing insights into the host immune response, modulation of the tumor microenvironment and residual disease burden. Previous studies reported that elevated NLR levels, both immediately within 1 week postoperatively and later, 5 years after diagnosis, were associated with poorer survival outcomes in BC ( 51 53 ).…”
Section: Discussionmentioning
confidence: 92%
“…The NLR is typically measured from a complete blood count (CBC) or blood test [16]. The NLR was proven to be a valuable marker in assessing inflammatory conditions such as autoimmune diseases and different forms of cancer [17][18][19][20]. Given that COVID-19 is characterized by a significant inflammatory component [21], it is comprehensible why researchers examined the NLR as a potential prognostic marker, recognizing its role in predictive assessments.…”
Section: Introductionmentioning
confidence: 99%